Intellectual Styles as Predictors of Academic Stress - Sompal; Yadav V.N. (International Journal of Indian Psychȯlogy, 2022)
Students have experienced academic stress over the years. According to studies, many students are having major issues as a result of the rising levels of academic stress. Despite additional aspects such as peer pressure, work load, academic environment and family expectations, academic stress still remains a big challenge. Intellectual styles are crucial in the control of academic stress. Students’ degrees of academic stress have been found to differ depending on their intellectual styles. Academic stress brings changes in daily routine and can alter the behaviour. Subsequently, if student’s academic stress is not dealt effectively, this may result in low academic performance. The main motive of the study intellectual styles as predictors of academic stress. The proposed study was carried out on a sample of 70 students in the age range of 18 to 25 years. Academic Stress Scale (Kumar et al., 2023) and Thinking Style Inventory (Sternberg, 1992) were used to measure the variables under study. Obtained data were analysed by using descriptive statistics, Pearson correlation and regression. Results revealed that the association between the variables intellectual styles and the academic stress was found to be significant. Regression analysis demonstrated that the internal intellectual style (IS) component of 13 intellectual styles was the predictor of academic stress.